Removal of hydrogen sulfide generated during anaerobic treatment of sulfate-laden wastewater using biochar: Evaluation of efficiency and mechanisms. (June 2017) - Kanjanarong, Jarupat; Giri, Balendu S.; Jaisi, Deb P.; Oliveira, Fernanda R.; Boonsawang, Piyarat; Chaiprapat, Sumate; Singh, R.S.; Balakrishna, Avula; Khanal, Samir Kumar
Graphical abstract: Highlights: High effectiveness of biochar for H2 S removal (98%) was achieved. Biochar after sulfide removal contained sulfate and sulfur on its surface and in pores, respectively. Sulfur/sulfate on biochar makes it lucrative for land application. Abstract: Removal of hydrogen sulfide (H2 S) from biogas was investigated in a biochar column integrated with a bench-scale continuous-stirred tank reactor (CSTR) treating sulfate-laden wastewater. Synthetic wastewater containing sulfate concentrations of 200–2000 mg SO 4 2 - / L was used as substrate, and the CSTR was operated at an organic loading rate of 1.5 g chemical oxygen demand (COD)/L·day and a hydraulic retention time (HRT) of 20 days. The biochar was able to remove about 98.0 (±1.2)% of H2 S for the ranges of concentrations from 105–1020 ppmv, especially at high moisture content (80–85%). Very high H2 S adsorption capacity (up to 273.2 ± 1.9 mg H2 S/g) of biochar is expected to enhance the H2 S oxidation into S 0 and sulfate. These findings bring a potentially novel application of sulfur-rich biochar as a source of sulfur, an essential but often deficient micro-nutrient in soils.